Pelvic inflammatory disease: Pathophysiology - Saona Ugarte, Pedro (2015)
Pelvic inflammatory disease (PID) may be difficult to diagnose due to the diverse clinical presentation, either patients severely ill or asymptomatic. Most common symptom is pelvic pain (90%) and others are dyspareunia, abnormal vaginal discharge or bleeding, voiding urgency, nausea, vomiting, and rectal tenesmus. On bimanual vaginal examination at least one of the following findings is essential: pain on cervix or uterus movilization or pain at adnexal palpation. Auxiliary tests can show leukocytes on vaginal secretion, increased erythrocyte sedimentation rate, and identification of Neisseria gonorrhea or Chlamydia trachomatis in the cervix. Other useful tests are imaging studies, including vaginal ultrasound, computed axial scan or magnetic resonance. Laparoscopy is the gold standard. Though there are reports on endometrial biopsy complementing PID diagnosis when there is no evidence of disease during laparoscopy. A low threshold is recommended for PID diagnosis because delay on treatment can increase either acute complications such as perihepatitis, periappendicitis, rupture of tubo-ovarian abscess, or chronic complications like chronic pelvic pain, infertility or ectopic pregnancy.